แนวทางการพัฒนาการบริหารเทคโนโลยีสารสนเทศและการสื่อสารของโรงเรียนวัดโกสินารายน์ - แซ่เฮ้ง, สุภัค; เก้าเอี้ยน, สุรศักดิ์ (An Online Journal of Education, 2018)
The research aimed to survey problems of an ICT management and the level of using ICT for Watkosinarai School’s tasks; in addition, to propose the approaches for the development of an ICT management of the school. 18 school staff consisted of the school principal and teachers were research respondents. The data were collected by using the questionnaire of approaches for the development of an ICT management of Watkosinarai School. The approaches for the development of an ICT management for Watkosinarai School verified by experts. Quantitative data was analyzed using frequency, distribution, percentage, mean and standard deviation, while content analysis was used for qualitative data analysis. The research results were 1) In overview, the problems of Watkosinarai School’s ICT management were high level. The highest level problem was resources and basic ICT infrastructures, staff, and ICT support issue accordingly. 2) The school used ICT for administration and documents task in the most. The second was curriculum development and teaching while the report revealed that school hardly used ICT in public relationship. 3) The approaches for the development of an ICT management of the school consisted of focusing on encouraging teachers to use ICT in their daily tasks, increasing the opportunity to attend ICT workshops for their ICT knowledge and skill development. Moreover, the principle and school board should seriously monitor any school tasks by using ICT, allocate the appropriate budget for ICT equipment and basic infrastructures providing and maintenance that made them were available to use efficiently. After confirming these results by interview experts, The approaches for the development of an ICT management of the school called ‘3SMART model’ was designed. There are 3 standing plans and 12 activity plans on the model. The details consisted of 3 approaches: 1) Smart System 2) Smart Organization and 3) Smart Staff.